2017
DOI: 10.1002/rcm.7816
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of soluble components in coals and interpretations for the complex mass spectra

Abstract: Interpretation methods for mass spectra visualize and simplify the understanding of complex components in coals for industrial utilization. Coals with a high concentration ratio for a specific class should take priority as a feedstock for chemicals and receive more attention. Copyright © 2016 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Improved analytical methods were emerged to take advantage on the characterization of species in biooil. HRMSs were extensively used to identify individual component according to the monoisotopic mass in complex mixtures [ 17 , 44 , 47 , 74 , 76 , 83 , 84 ].…”
Section: Introductionmentioning
confidence: 99%
“…Improved analytical methods were emerged to take advantage on the characterization of species in biooil. HRMSs were extensively used to identify individual component according to the monoisotopic mass in complex mixtures [ 17 , 44 , 47 , 74 , 76 , 83 , 84 ].…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Moreover, carbon emission and acid rain mostly induced by coal burning led us to reconsider the utilization of coal in clean and highly efficient ways. 4,5 Lignite is unsuitable for direct burning, but suitable for developing as a feedstock for value-added chemicals due to the high content of organic oxygen. [6][7][8] It is reasonable to utilize lignite for non-fuel purposes and important to understand the molecular composition of the organic species present in lignite.…”
Section: Introductionmentioning
confidence: 99%
“…Data 13–15 (obtained by ESI−) contain relatively higher contents of compounds from the O 4 –O 6 classes. Previous research has shown that a high number of oxygen atoms per molecule causes an increased polarity and the molecule is more facile to be ionized by ESI compared with APPI . Compounds in the ON class are widely detected by ESI‐MS.…”
Section: Resultsmentioning
confidence: 99%
“…However, there are large amounts of compounds from the N and ON classes in group 1 because ESI+ is more suitable to detect alkaline compounds . Combining the loading plot with the score plot, groups 2 and 3 mainly contain the compounds from the ON, OS, N and NS classes, while no compound from the CH class was detected in all of the extracts because hydrocarbons are difficult to protonate in the positive mode of ESI …”
Section: Resultsmentioning
confidence: 99%